PENGARUH LITERASI KEUANGAN, MODAL MANUSIA, DAN FINANCIAL TECHNOLOGY TERHADAP KINERJA UMKM DI KABUPATEN SLEMAN - Reza Wulan Sari; Sri Widodo (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study was conducted to determine the effect of financial literacy, human capital, and financial technology on the performance of MSMEs in Sleman Regency. In addition, this study was also conducted to reveal whether financial literacy, human capital, and financial technology can increase the income of MSMEs. The research method used in this study is a quantitative approach using a questionnaire as a research instrument and focusing on the object of 100 culinary SMEs in the Sleman Regency area. The tests used in this study include the Multiple Linear Regression Test conducted using SPSS. The results of this study indicate that financial literacy, human capital, and financial technology have a significant effect on the performance of MSMEs in Sleman Regency. This is indicated by the SPSS calculation with the significance value of each variable <0.05.